Propuesta de implementación del Balanced Scorecard para medir la gestión estratégica de la empresa Qumir SAC del año 2018 - Luna Guerrero, Anthony Bryan (2019)
ABSTRACT The present work deals with the development of a Balanced Scorecard implementation proposal to measure the strategic management of the Qumir SAC company of the year 2018, through all the components of the Balanced Scorecard, wich are the four perspectives of the Balanced Scorecard (financial perspective, client perspective, internal processes perspective and, perspective of the learning and growth), the strategic map, the goals, strategic actions and responsibles. For the development of the Balanced Scorecard proposal, the following methodology was used: situational diagnosis of the company, analysis of the company's external internal environment (SWOT), strategic map design and preparation of the Balanced Scorecard matrix. The results obtained from the external internal analysis of the organization as well as its strategic planning (mission, vision and values), allowed to design the strategic map of the company and to elaborate the matrix of the Balanced Scorecard (BSC), in which all its components are reflected. Therefore, it is concluded that the implementation of all these components will allow the company to determine compliance with the strategic’s objectives and indicators set for its growth, in order to achieve the desired profitability.